PHYSIC AND CHEMICAL PROPERTIES OF ALLOYED METALLURGICAL WASTE AS A SECONDARY RESOURCE-SAVING SUBSTANCE - Pavlov, Vasyl; Skachkov, Viktor; Yanko, Taras (Scientific Journal "Metallurgy", 2021)
The hydrogenation process is released in three stages on spongy titanium grade TG-100 with a particle size in the range from 2 to 5 mm. At the first stage, the hydrogenation process was carried out on the starting material – spongy titanium with particle sizes of –12 + 5 and –30 + 10 mm. At the second stage of hydrogenation, mechanically activated TG-100 was used. At the third stage of hydrogenation, a mixture of mechanically activated TG-100 with titanium hydride was used. In the process of titanium hydride formation four main stages are defined: physical adsorption of hydrogen molecules on the metal surface; dissociation of hydrogen molecules on active centers of the metal surface; diffusion of hydrogen atoms into the surface layer of the metal and the ordered placement of hydrogen in the voids of the metal matrix with the formation of a hydride (β-phase). It was found that the temperature of the beginning of active absorption of hydrogen for the initial TG-100 is 693 K, for mechanically activated titanium spongy – 573 K, and for mechanochemically activated material – 503 K. The total hydrogenation time of the initial TG-100 was 1380 minutes, for mechanically activated – 1140 minutes and for mechanochemically activated – 780 minutes. The mechanochemical activation of titanium sponge made it allows to fulfil the duration of the hydrogenation process by almost 46 %. In this case, the mass fraction of hydrogen in titanium hydride ranged from 3.63 % to 3.84 % by mass, the maximum process temperature was set in the range from 590 °C to 645 °C, and the time to reach the maximum temperature was from 120 minutes to 240 minutes. The yield of titanium hydride before reaching the maximum temperature was 35.4 % for the initial TG-100, 50.0 % for mechanically activated, and 59.4 % for mechanochemically activated.